Deciphering the binding behaviours of BSA using ionic AIE-active fluorescent probes. (8th December 2016) - Tong, Jiaqi; Hu, Ting; Qin, Anjun; Sun, Jing Zhi; Tang, Ben Zhong
Abstract : The binding behaviours of a transport protein, bovine serum albumin (BSA), in its native, unfolding and refolding states have been probed by monitoring the emission changes of two exogenous AIE-active fluorescent probes, M2 andM3, which are designed to be anionic and cationic, respectively. Due to their AIE properties, bothM2 andM3 display emission enhancement when bound to the hydrophobic cavity of BSA. The binding site ofM2 andM3 is found to be subdomain IIA. Then, the BSA +M2 and BSA +M3 systems are utilized to fluorescently signal the conformation changes of BSA caused by various external stimuli, including thermally or chemically induced denaturation. The data confirmed the multi-step unfolding process and the existence of a molten-globule intermediate state. The unfolding process consists of the rearrangement of subdomain IIA, the exposure of a negatively charged binding site in domain I that prefers interacting with cationic species, and the transformation of the molten-globule intermediate into the final random coil. The anionic and cationic modifications of the probes enable us to observe that electrostatic interactions play a role in the folding and unfolding of BSA.